Cookie Truck: A Sugar Cookie Shapes Book a sugar cookie shapes book - Wright, Caroline; Oliver, Alison (New York, NY : Harper Festival, an imprint of HarperCollinsPublishers, 2021)
Little bakers will love this interactive concept book in which a truck made out of sugar cookies of all shapes drives them right to the kitchen where they can make a kid-friendly recipe for homemade sugar cookies.
Cover title
On board pages
New Kids Book 2022 Fall.
Keywords: Cookies -- Juvenile fiction; Baking -- Juvenile fiction; Shapes -- Juvenile fiction; Trucks -- Juvenile fiction; Stories in rhyme; Fiction